Appraisal, feedback and development : making performance review work - Fletcher, Clive (London ; New York : Routledge, 2008)
Tried and trusted by thousands of HRM students and professionals in three previous editions, this is the most comprehensive introduction to performance appraisal currently available.
Appraisal today -- Deciding on the aims of appraisal -- The content of appraisal -- Appraisal as an element in performance management -- Designing appraisal systems, and the use of IT -- Multi-level, multi-source feedback systems -- Best practice and current trends in multi-source feedback -- Training, and the implementation of appraisal -- Monitoring and maintenance -- Appraising, identifying and developing potential -- Appraisal with professionals, and in the public sector -- Cultural challenges in applying performance appraisal -- Appraisal: the way ahead -- Appendixes: A. Example of appraisal scheme documents -- B. Attitude measures.
Revised edition of: Appraisal and feedback. 3rd ed. 2004.
Includes bibliographical references (pages 199-209) and index.
Keywords: Employees -- Rating of; Performance standards; Personnel -- Évaluation.; Rendement au travail -- Normes; Employees -- Rating of; Performance standards; Personeelsbeoordeling